ANALISIS KEBIJAKAN PENGELOLAAN HUTAN RAKYAT UNTUK MENDORONG FUNGSI LINDUNG - Alan Purbawiyatna; Hariadi Kartodihardjo; Hadi Sukadi Alikodra; Lilik Budi Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2012)
Community forest that privately owned at Kuningan Regency, West Java Province, have showed forest cover improvement at average of 5.86% during 2003 –2009. The main factor which contributes to this improvement was economic motivation of owners as a response to growing market of timber originated from community forest. This forest potentially serves as protected area outside state forest in land use plan of Kuningan district. Due to its characteristic as common-pool resources in the context of its protection function, privately owned community forest requires certain institutional arrangement to enable sustainable forest management resulting sustainable benefit for public. The aim of this study is to assess policy framework and its implementation designed to promote sustainable community forest development. The framework for implementation analysis was applied in this research with emphasis on the policy variable. The result showed that existing policy framework is weak to support sustainable management of community forest. They were characterized by unclear formulation of concepts in policy documents, inappropriate causal theory, unbalance financial resource allocation, very much detail and almost rigid in technical guidelines thereby hindering the achievement of policy objectives. Keywords: community forest, sustainable forest management, policy variable, policy analysis